Green human resource management and sustainable workplace: Artificial Intelligence as mediating variable - Mahat, Dipak; Shrestha, Sajeeb Kumar; Neupane, Dasarath; Karki, Tej Bahadur; Dongol, Padam (Edelweiss Applied Science and Technology, 2025)
The purpose of this study is to investigate how Artificial Intelligence (AI) mediates the relationship between Green Human Resource Management (GHRM) practices and the development of sustainable work environments. As sustainability becomes a growing concern in modern workplaces, GHRM has emerged as a vital approach to promoting eco-friendly practices. This study was grounded in the philosophy of positivism and employed an explanatory research design. Data were collected through a survey of 400 employees from eight commercial banks, representing public, private, and development sectors. The sample primarily consisted of a youthful workforce, with most participants holding bachelor’s degrees. The findings highlight AI as a critical mediator, enhancing the effectiveness of GHRM practices and promoting sustainable workplace outcomes. This research offers novel insights into AI’s role in advancing GHRM and sustainability, particularly in developing nations like Nepal. It emphasizes the importance of integrating AI into HRM models to achieve transformative and sustainable organizational practices, providing practical implications for the banking sector and beyond.